Develeopment e-modules based android in Newton's law topic for senior high school - Eriyanti, Ira Lelita; Jumadi, Jumadi; Yanarti, Yanarti; Rosiningtias, Wiwin (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
Developing android-based teaching materials is an initial step to follow the presence of the society 5.0 era in the learning system. This study aimed to know the feasibility and practicality of an Android-based e-module developed on Newton's law material. This study is research and development using the 4D model from Thiagarajan with four stages of development: define, design, develop, and dissemination. The research instrument used is an expert validation sheet, students' reliability questionnaire, interview guide sheet, and e-module prototype with research subjects consisting of 50 students. The research instruments used are expert validation sheets, student reliability questionnaires, interview guide sheets, and e-module prototypes. The research subjects are 10th-grade students. The data analysis technique is quantitative descriptive. Based on expert validation, the feasibility analysis results show 94.86% and 90.8%. Results of the practicality analysis show a percentage of 100% based on the test results, which means that the android-based e-module developed meets the feasibility and practical aspects of teaching materials on Newton's law. The effective analysis results on the effective use of e-modules show N-gain 1,877 in the high category, which means that e-module developed is effective use as learning media in Newton's law material.